Hypoxia inhibits nephrogenesis through paracrine Vegfa despite the ability to enhance tubulogenesis - Schley, Gunnar; Scholz, Holger; Kraus, Andre; Hackenbeck, Thomas; Klanke, Bernd; Willam, Carsten; Wiesener, Michael; Heinze, Eva; Burzlaff, Nicolai; Eckardt, Kai-Uwe; Buchholz, Björn (Kidney International, 2015)
Reduced nephron number predisposes to hypertension and kidney disease. Interaction of the branching ureteric bud and surrounding mesenchymal cells determines nephron number. Since oxygen supply may be critical for intrauterine development, we tested whether hypoxia and hypoxiainducible factor-1 alpha (HIF-1 alpha) influence nephrogenesis. We found that HIF-1 alpha is required for branching of MDCK cells. In addition, culture of metanephric mouse kidneys with ureteric bud cell-specific stabilization or knockout of HIF-1 alpha revealed a positive impact of HIF-1 alpha on nephrogenesis. In contrast, widespread stabilization of HIF-1 alpha in metanephric kidneys through hypoxia or HIF stabilizers impaired nephrogenesis, and pharmacological HIF inhibition enhanced nephrogenesis. Several lines of evidence suggest an inhibitory effect through the hypoxia response of mesenchymal cells. HIF-1 alpha was expressed in mesenchymal cells during nephrogenesis. Expression of the anti-branching factors Bmp4 and Vegfa, secreted by mesenchymal cells, was increased upon HIF stabilization. The conditioned medium from hypoxic metanephric kidneys inhibited MDCK branching, which was partially rescued by Vegfa antibodies. Thus, the effect of HIF-1 alpha on nephrogenesis appears context dependent. While HIF-1 alpha in the ureteric bud is of importance for proper branching morphogenesis, the net effect of hypoxia-induced HIF activation in the embryonic kidney appears to be mesenchymal cell-dependent inhibition of ureter branching.
EVALuna2:3775
Keywords: hypoxia; hypoxia-inducible factor-1 alpha; kidney development; metanephric mesenchyme; nephrogenesis; Vegfa